KNOWLEDGE MANAGEMENT TECHNOLOGIES IN VIEW OF IMPLEMENTATION OF QUALITY MANAGEMENT - L. Anisimova; V. Pryimak (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The paper reveals actual problems of development and implementation of international quality standards. Authors proposed KM-oriented model of organizational learning both in view of implementation of total quality management concept and realization of enterprise’s principal activity in general.